Great Britain and the opening of Japan, 1834-1858 (Luzac, 1951)
This book consists of the following many parts: introduction the seventeeth century, company and crown, the opium war in Anglo-Japanese relations, secret plans, the perry expedition 1852-54, the strirling bowring and the foreign office 1854-57, the elgin mission 1857-57.